Outcome and Toxicity of an Ifosfamide-Based Soft Tissue Sarcoma Treatment Protocol in Children. The Importance of Local Therapy. (1998) - Yule, S. Murray; Skinner, Roderick; English, Martin W.; Cole, Mike; Pearson, Andrew D. J.; Lucraft, Helen H.; Craft, Alan W.
Abstract : Background. Although the survival of children with soft tissue sarcoma (STS) has improved considerably, the outcome of patients with metastatic disease, and those with primary tumours of the extremities or parameningeal sites remains disappointing. We describe the clinical outcome of an ifosfamide-based regimen with local therapy directed only to children who failed to achieve a complete response to initial chemotherapy. Patients and Methods. Twenty-one children with STS (16 rhabdomyosarcoma) who presented with unresectable tumours were treated with five courses of ifosfamide (9 g/m 2 ) and etoposide (600 mg/m 2 ). Patients who did not achieve a complete response then received local therapy. Chemotherapy with ifosfamide combined with etoposide, vincristine (1.5 mg/m 2 and doxorubicin (60 mg/m 2 ) or vincristine and actinomycin D (1.5 mg/m 2 ) was continued for one year. Results and Discussion. Objective responses to five courses of ifosfamide and etoposide were seen in all patients. Disease free survival (DFS) at a median follow up of 59 months was 57% (95% CI 29–75%). The DFS of children who received local therapy was 89% compared with 33% in those who received chemotherapy alone ( p =0.027). Locoregional recurrences did not occur in children who received radiotherapy to the site of the primary tumour. Ifosfamide-based chemotherapy does not reduce the incidence of loco-regional recurrence in children who do not receive local therapy.